CELIAC DISEASE IN ASIA BEYOND THE MIDDLE EAST AND INDIAN SUBCONTINENT: EPIDEMIOLOGICAL BURDEN AND DIAGNOSTIC BARRIERS - Poddighe, Dimitri; Abdukhakimova, Diyora (Baishideng Publishing Group Co, 2021)
Celiac Disease (CD) had been considered uncommon in Asia for a long time. However, several studies suggested that, in the Indian subcontinent and Middle East countries, CD is present and as prevalent as in Western countries. Outside these Asian regions, the information about the epidemiology of CD is still lacking or largely incomplete for different and variable reasons. Here, we discuss the epidemiological aspects and the diagnostic barriers in several Asian regions including China, Japan, Southeast Asia and Russia/Central Asia. In some of those regions, especially Russia and Central Asia, the prevalence of CD is very likely to be underestimated. Several factors may, to a different extent, contribute to CD underdiagnosis (and, thus, underestimation of its epidemiological burden), including the poor disease awareness among physicians and/or patients, limited access to diagnostic resources, inappropriate use or interpretation of the serological tests, absence of standardized diagnostic and endoscopic protocols, and insufficient expertise in histopathological interpretation.
Keywords: Asia; Celiac disease; Central Asia; China; Diagnostic barriers; Epidemiology; HLA-DQB1; Japan; Prevalence; Russia; Type of access: Open Access; Research Subject Categories::MEDICINE